-4(1-x)+1=3x+5

Simple and best practice solution for -4(1-x)+1=3x+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(1-x)+1=3x+5 equation:


Simplifying
-4(1 + -1x) + 1 = 3x + 5
(1 * -4 + -1x * -4) + 1 = 3x + 5
(-4 + 4x) + 1 = 3x + 5

Reorder the terms:
-4 + 1 + 4x = 3x + 5

Combine like terms: -4 + 1 = -3
-3 + 4x = 3x + 5

Reorder the terms:
-3 + 4x = 5 + 3x

Solving
-3 + 4x = 5 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-3 + 4x + -3x = 5 + 3x + -3x

Combine like terms: 4x + -3x = 1x
-3 + 1x = 5 + 3x + -3x

Combine like terms: 3x + -3x = 0
-3 + 1x = 5 + 0
-3 + 1x = 5

Add '3' to each side of the equation.
-3 + 3 + 1x = 5 + 3

Combine like terms: -3 + 3 = 0
0 + 1x = 5 + 3
1x = 5 + 3

Combine like terms: 5 + 3 = 8
1x = 8

Divide each side by '1'.
x = 8

Simplifying
x = 8

See similar equations:

| 0.8n-1.5n+30=54 | | 4x-3(x-8)=4+2x | | 8+y=-5 | | 8(m-8)=80 | | 44(10+5x)=-100 | | -11-2n=n+4 | | 0.8n+1.5n-30=54 | | 2x+5x+4x=25 | | y=x^3-2x^2-8x | | 2sin(2x)=-tan(2x) | | -5=9+2c | | 16+8n= | | 10-2(x+3)=-5x+6 | | 7(n+5)=35+7n | | 5c^4+10c^2+5= | | 7x+8=7(x+2) | | -2b=9-3a | | 1+4x=9+2x | | X^3-21x^2+120x=0 | | 3X^2(2X^3+8X^2-5X+6)= | | -11=3u+7 | | 24+6k=4(k+4) | | 5(2x+8)=2x-64 | | 20m=420 | | 6+2y=-4 | | 2y=-7x+10 | | 4(7x+8)=32 | | -5(a+4)=-11-8a | | -8+(-4)=q | | 3(3x+8)=9x-1 | | 7q=11+p | | 4(x+2)-2x=20-2x |

Equations solver categories